Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran IPA dengan Materi Pokok Manusia dan Lingkungan Menggunakan Metode Berjubel (Belajar dengan Bermain Jual Beli) pada Siswa Kelas VII SMP Negeri 21 Mataram - Rahmawati, Lindu (Lembaga Yasin AlSys, 2023)
The purpose of this study was to determine the increase in the activity and learning outcomes of science on the subject of Population Density in relation to the Environment and the material on Pollution and Environmental Damage in relation to human activity for class VII students of SMP Negeri 21 Mataram in the Academic Year 2022/2023 through the use of the Judgment method. This research was conducted at SMP Negeri 21 Mataram in the 2022/2023 academic year with research subjects being class VII students consisting of 14 male students and 14 female students. The method used is the Classroom Action Research method which consists of two cycles. In the first cycle, learning was carried out using the Jubel method in large groups, while in the second cycle, the Jubel method was used in small groups. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning activities and learning outcomes. The results of this study indicate that: First, the use of the Jubilee method can increase science learning activities on population density in relation to the environment and environmental pollution and damage in relation to human activity for class VII students of SMP Negeri 21 Mataram semester of the 2022/2023 academic year. It is proven that the percentage of students in the good learning activity category increased from the initial conditions of 29% to 64% in cycle I and to 82% in cycle II or in the final conditions there was an increase of 51% from the initial conditions. Second, the use of the Jubilee method can improve science learning outcomes on population density in relation to the environment and environmental pollution and damage in relation to human activity for class VII students at SMP Negeri 21 Mataram in the 2022/2023 academic year. It is proven that the percentage of student learning completeness increased from the initial conditions of 57% to 64% in cycle I and to 74% in cycle II or in the final conditions an increase of 17% from the initial conditions.